Development of Transactional Communication Model for Midwife and Postpartum Mother on Exclusive Breastfeeding - Rekawati Susilaningrum; Sri Utami; Susilorini Susilorini (Jurnal Ners, 2017)
Introduction. Exclusive breastfeeding has become a major issue in Surabaya because the number of exclusive breastfeeding coverage are less than 80% which is below the national target. The purpose of this study was to develop a transactional communication model based on management between midwife and postpartum mother on exclusive breastfeeding.Method. The design used in this study was cross-sectional with 175 postpartum mothers in public health center Surabaya as the samples that recruited by purposive sampling. Questionnaires were used as instrument and data were analyzed by using descriptive statistical test and Partial Least Square (PLS). Result. The result showed that predisposing factors and enabling factors were able to improve the practice of exclusive breastfeeding directly or indirectly by transactional communication with t-table (>1.96). However, reinforcing factors could not directly improve the practice of exclusive breastfeeding. This study indicates that practice of exclusive breastfeeding could be improved with transactional communication based on human interaction theory.Conclusion. The implementation of transactional communication between midwife and mother would be able to optimize the predisposing factors, enabling factors, and reinforcing factors on the practice of exclusive breastfeeding.